Factors And Patterns Of Interaction Towards The Development Of Webbased Instructional Evolution Tool For Technology Integration Among School Teachers - Mohd Johari, Siti Sarah (2023)
Technology has been playing an increasingly important role and has made its way into the classroom environment as a result of its irrefutable presence in today's education. The percentage use of technology in the classroom was still lagging behind its expectations. Unresolved issues such as underutilization of provided platforms or coursewares, as well as teacher resistance to them remained unresolved and lacking in evidence. The majority of Malaysian teachers are not aware of softwares or websites that could assist them improve teaching and learning, and just a small fraction of teachers have received professional training in ICT fundamentals. The aim of this research is to look into the challenges or gaps in technology integration among teachers in school classrooms while in these initiatives.Thus interaction patterns in the classroom can be discovered to aid in the development of an identifier of teachers' potential technology skills.As such, in order to conduct the case study, three students from standard one and ten students from form two were selected to serve as a focus group, along with two primary school teachers and one secondary school teacher.The first phase of the research will determine how much influence the introduced factors have on interactions in the classrooms.